2020
DOI: 10.2196/17417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Safety and Efficacy of Follow-up for Patients With Abdominal Pain Using Video Consultation (SAVED Study): Randomized Controlled Trial

Abstract: Background The benefits of telemedicine include cost savings and decentralized care. Video consultation is one form that enables early detection of deteriorating patients and promotion of self-efficacy in patients who are well but anxious. Abdominal pain is a common symptom presented by patients in emergency departments. These patients could benefit from video consultation, as it enables remote follow-up of patients who do not require admission and facilitates early discharge of patients from overc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…This was illustrated in the SAVED study operationalizing telehealth for complexed emergency services ( 51 ). Digital operationalization of mental health services can be similarly achieved using combinations of digital tools in comprehensive services such as Illness Management and Recovery (IMR) Programs ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was illustrated in the SAVED study operationalizing telehealth for complexed emergency services ( 51 ). Digital operationalization of mental health services can be similarly achieved using combinations of digital tools in comprehensive services such as Illness Management and Recovery (IMR) Programs ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Participatory approaches like these with design-thinking have been used to operationalize tele-health in complexed emergency services ( 51 ), as well as develop solutions with targeted applications such as AI chatbots for automated adolescent mental health coaching ( 54 ). In tandem, it is important to address the needs of vulnerable populations that may fail to seek care, such as potential domestic violence or child abuse victims ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…13,55 Technology combinations that have been similarly applied outside ophthalmology include the Babylon conversational AI-chat bots that triage patients and refer those requiring further assessment onwards for a video consultation. 56 Hybrid telehealth (the stacked combination of digital and physical clinical services) has also been illustrated in the SAVED trial of text-based asynchronous reviews with synchronous video consultations at emergency services in Singapore, 57 highlighting its potential to facilitate early discharge and reduce time in hospitals.…”
Section: Front-line Operational Modelsmentioning
confidence: 99%
“… 14 These considerations can be incorporated together in a well-planned study using approaches such as design thinking, 15 as illustrated in the SAVED trial of hybrid synchronous-asynchronous digital telereview of patients with acute undifferentiated abdominal pain. 16 The SAVED trial demonstrated effective operationalisation of a digital telehealth intervention along with potential manpower and time savings that are much needed to expand service capacity in the context of the ongoing pandemic.…”
Section: Digital Telehealth Platformsmentioning
confidence: 99%
“…This ‘sorting conveyor’ model is beneficial to leverage digital solutions to address the needs of patients and reduce unnecessary healthcare presentations, thereby helping to reduce risks of healthcare associated transmission of COVID-19. 16 That said, a recent review reported that most healthcare applications of chat bots lack sufficient validation of clinical outcomes. 25 This is a crucial step that is needed for these solutions to be safely deployed.…”
Section: Conversational Artificial Intelligencementioning
confidence: 99%